The Development of Gymnospremae Interactive Media Android Based with The Discovery Learning to Improve Student Learning Result on Plantae Subject in Senior High School - Amalia, Isna Rizqi; Rahayu, Enni Suwarsi; HB, Putut Martin (FMIPA UNNES, 2020)
Plantae is one of biology subjects at X grade. The school condition that located in the low area causing not so many diversity of plant in the school environtment and there is no Gymnospermae. The learning method still using lecture with the help of power point and also teacher and student manual book. Students less active and do not really engage in the learning process so it influence the learning result. The aim of this study is to develop Gymnospremae Interactive Media Android Based (MIGA) with The Discovery Learning towards Plantae Subject in Senior High School. This study is a research and development (R&D) study with the phases of data collection, product design, product validation, product revision small scale testing, product revision, huge scale testing, product revision and final product. The assessment result of MIGA validation by subject expert is 91,67% (very valid) and by media expert is 100% (very valid). The media effectiveness which is seen from students learning result based on pre test and post test showed that there was an improvement of knowledge with N-gain average of 0,49 (moderate) and students classical thoroughness of 100%. Besides, MIGA is mentioned as a very practical based on the assessment of teacher’s response in the amount of 85,41% and students in the amount of 83,12%. Based on the analysis of research result, it can be concluded that the developed MIGA is valid, effective, and practical in the learning process.